HUBUNGAN PERSEPSI REMAJA TENTANG PERNIKAHAN DINI DENGAN NIAT UNTUK MENIKAH DINI PADA REMAJA MASYARAKAT MADURA - Yessy Nur Endah Sary (LPPM Universitas Abdurrab, 2025)
Adolescents, as the next generation approaches this stage of life, need to have a clear understanding of what it means to be marriage ready. Views and the possibility of changes in outlook on marriage and preparation impact the perception of early marriage. The researchers in this study set out to answer the question,